The structural and optical properties of neodymium doped lithium niobate and yttrium aluminum garnet single crystals - Zainal Abidin Sham, Nurul Wahidah (2015)
A Neodymium doped Lithium Niobate (LiNbO3) single crystal of composition (48.6 - y) Li2CO3 + (51.4) Nb2O5 + (y) Nd2O3, (y = 0.5, y = 1.0) and a Neodymium doped Yttrium Aluminum Garnet (YAG) single crystal of composition (31 - y) Y2O3 + (69.0) Al2O3+ (y) Nd2O3, (y = 0.5, y = 1.0) were prepared by using Czochralski technique. The structural and optical properties of the crystals along the boule were investigated. The dopant concentration is varied along the crystal boule. The FTIR spectra of the Nd: LiNbO3 crystals show that there are slight to the peaks at peaks of 3243 cm-1 - 3251 cm-1 when the content of Nd2O3 is increased and this shows the existence of OH bond stretching. In addition, the presence of the IR band in the range of 3567 cm-1 - 3572 cm-1 shows that the OH bond is due to the defect of the crystals while fundamental stretching of OH groups can be assigned to a band in the range of 3846 cm-1 - 3866 cm-1. As for the Nd: YAG crystals, sharp peaks are observed at 698 cm-1 and 748 cm-1 which can be assigned to Y – O symmetrical stretching and Y – O asymmetrical stretching, respectively. The first peak shifts slightly from 698 cm-1- 699 cm-1 and the second peak from 748 cm-1 - 751 cm-1 as the content of Nd2O3 in the system is increased. In addition, a band in the range of 801 cm-1 - 803 cm-1 is assigned to Y – O bonds which have strong metal-oxygen stretching vibrations in tetrahedral arrangement. The IR peaks at 3290 cm-1 - 3369 cm-1 show the fundamental stretching of OH groups. The UV–Vis–NIR spectroscopy of Nd: LiNbO3 crystals show that the values of indirect optical band gaps lie between 2.78 eV to 2.57 eV and those of the direct optical band gaps are between 3.82 eV to 3.71 eV. The Urbach energy for the Nd: LiNbO3 crystal decreases from 0.69 eV to 0.48 eV. The UV–Vis–NIR spectroscopy of Nd: YAG crystals show that the values of indirect optical band gaps lie between 1.99 eV to 2.10 eV and those of the direct optical band gaps lie between 4.83 eV to 4.85 eV. The Urbach energy for the Nd: YAG crystal decreases from 2.44 eV to 2.09 eV. The change in band gaps is associated with the structural change occurring after the addition of Nd2O3 as the dopant in the crystal system. Luminescence spectra of Nd: LiNbO3 crystals show that there is a 2G9/2 ?4I9/2 transition corresponding to a green emission at 492 nm and a 2H11/2 ?4I9/2 transition corresponding to an orange emission at 621 nm. As for Nd: YAG crystals, there is a 2G11/2 ?4I9/2 transition corresponding to a blue emission at 449 nm and a 2G9/2 ?4I9/2 transition corresponding to a cyan emission at 490 nm. As a conclusion, the two crystal systems show that the increase of Nd2O3 dopant from 0.5% mol to 1.0% mol will contribute to the decrease of crystal defects.